Building lives with dignity - Oakes, Eva (Technical Centre for Agricultural and Rural Cooperation, 2018)
Eva Oakes describes Choco4Peace's experience building a network based on blockchain technology in the cocoa sector in Colombia. The main aim is to get smallholders out of both cocaine production and poverty through access to finance.